2009
DOI: 10.1063/1.3237158
|View full text |Cite
|
Sign up to set email alerts
|

Combined temperature-programmed reaction and in situ x-ray scattering studies of size-selected silver clusters under realistic reaction conditions in the epoxidation of propene

Abstract: Atomically precise (catalytic) particles synthesized by a novel cluster deposition instrument

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 51 publications
(23 reference statements)
3
30
0
Order By: Relevance
“…The drop in activity coincides with the region where a fine change in particle shape, without indication of sintering takes place. Similar distinct changes in catalytic performance following changes in particle morphology were reported for example for small Cu and Ag nanoparticles, 25,47 however some coking of Pt cannot be fully excluded. A stable ethene conversion of 0.12% and 0.08% was determined for small and large Pt particles, respectively, in good accord with the results obtained on B15 nm sized Pt particles tested under similar conditions.…”
Section: Hydrogenation Of Ethene With Deuteriumsupporting
confidence: 69%
See 1 more Smart Citation
“…The drop in activity coincides with the region where a fine change in particle shape, without indication of sintering takes place. Similar distinct changes in catalytic performance following changes in particle morphology were reported for example for small Cu and Ag nanoparticles, 25,47 however some coking of Pt cannot be fully excluded. A stable ethene conversion of 0.12% and 0.08% was determined for small and large Pt particles, respectively, in good accord with the results obtained on B15 nm sized Pt particles tested under similar conditions.…”
Section: Hydrogenation Of Ethene With Deuteriumsupporting
confidence: 69%
“…The altered surface energy might be caused by adsorbed carbon species that were left on the Pt surface during reaction. 54,55 Similar dynamic shape transformations were observed from GISAXS during the epoxidation of propene on size-selected silver nanocatalysts by Vajda et al 25 It was suggested that propene ligands might alter the surface energy of the particles and the strength of interaction to the support.…”
Section: Hydrogenation Of Ethene With Deuteriumsupporting
confidence: 62%
“…The reaction products were monitored using a differentially pumped mass spectrometer (Pfeiffer Prisma Plus). [23] Reference TPRx runs under identical reaction conditions were performed using a blank HOPG substrate (i.e. without clusters) for background correction -the TPRx signal acquired on the blank support was subtracted from the TPRx signal collected on the cluster samples -to obtain the TPRx signal produced by the clusters only.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] Thus, exploring the chemical properties of such model systems under realistic reaction conditions is now a hot topic. [19][20][21][22][23][24] The catalytic oxidation of alkanes to produce more valuable chemical intermediates such as alkenes is of both academic [25][26][27] and industrial interest. [28,29] Industrially, oxidation of cyclohexane is performed over cobalt-based catalysts in the liquid phase, showing low conversion but high selectivity towards cyclohexanol and cyclohexanone.…”
Section: Introductionmentioning
confidence: 99%
“…Harbich and co-workers have carried out STM and reactivity studies of deposited clusters, and recently reported studies focusing on the fundamentals of CO oxidation over Pt n /TiO 2 [72,73], and of electrocatalysis, using an approach where Pt clusters are deposited directly on a solid electrolyte, allowing electrochemistry to be studied in vacuo [7,74]. The Vajda group has an active program where size-selected catalysts are studied in a variety of reactors, recently focusing on in operando studies using tools such as X-ray scattering, to probe chemistry under realistic reaction conditions [4,9,10,[75][76][77][78][79][80][81][82][83]. Buratto and coworkers have used cluster deposition in conjunction with STM and theory to examine stability and reactivity of several types of clusters on TiO 2 (110), with recent work focusing on vanadia clusters on titania [84].…”
Section: Introductionmentioning
confidence: 99%